Anti-Inflammatory, Antidiabetic Properties and In Silico Modeling of Cucurbitane-Type Triterpene Glycosides from Fruits of an Indian Cultivar of Momordica charantia L. - Perera, Wilmer H. (Molecules, 2021)
Diabetes mellitus is a chronic disease and one of the fastest-growing health challenges of the last decades. Studies have shown that chronic low-grade inflammation and activation of the innate immune system are intimately involved in type 2 diabetes pathogenesis. Momordica charantia L. fruits are used in traditional medicine to manage diabetes. Herein, we report the purification of a new 23-O-β-d-allopyranosyl-5β,19-epoxycucurbitane-6,24-diene triterpene (charantoside XV, 6) along with 25ξ-isopropenylchole-5(6)-ene-3-O-β-d-glucopyranoside (1), karaviloside VI (2), karaviloside VIII (3), momordicoside L (4), momordicoside A (5) and kuguaglycoside C (7) from an Indian cultivar of Momordica charantia. At 50 µM compounds, 2–6 differentially affected the expression of pro-inflammatory markers IL-6, TNF-α, and iNOS, and mitochondrial marker COX-2. Compounds tested for the inhibition of α-amylase and α-glucosidase enzymes at 0.87 mM and 1.33 mM, respectively. Compounds showed similar α-amylase inhibitory activity than acarbose (0.13 mM) of control (68.0–76.6%). Karaviloside VIII (56.5%) was the most active compound in the α-glucosidase assay, followed by karaviloside VI (40.3%), while momordicoside L (23.7%), A (33.5%), and charantoside XV (23.9%) were the least active compounds. To better understand the mode of binding of cucurbitane-triterpenes to these enzymes, in silico docking of the isolated compounds was evaluated with α-amylase and α-glucosidase.